DINAMIKA ISLAM KONTEMPORER - Muhammad Haritz Arrasyid; M. Farhan Al-Hakim; Dhea Fadillah Yusuf (Adabiyah Islamic Journal, 2023)
The dynamics of Contemporary Islam is the condition of Islam that is influenced by modernization or the current state of Islam, along with social dynamics that are continuing and growing, according to the nature of the universe, these changes should be balanced with efforts to increase the reflection of Islamic intellectualism in this country. It is a fact that must be acknowledged, that Islamic values and cultural systems that exist in society have lost their dynamic power and become stagnant, so that they are unable to realize their role and function as rahmatan li al-'alamin. However, the era of globalization and information actually provides ample opportunities to realize the mission of Islam as rahmatan li al-'alamin.